Trans-cervical resection of a separate substernal goitre. (2017) - To, Henry; Karmakar, Antara; Farrell, Stephen; Manolas, Steve
Highlights: A separate substernal goitre is an unusual entity, which may have embryological origin as ectopic thyroid tissue, or residual cervical thyroid tissue following prior thyroid resection. Pre-operative imaging via a thyroid nuclear scan and computer tomography (CT) imaging aids in determining its characteristics and for pre-operative planning. A trans-cervical resection is preferred due to lower morbidity. A trans-cervical resection is achievable when the lesion is accessible and delivered through the thoracic inlet according to CT characteristics. Abstract: Introduction: A separate substernal goitre which is not continuous with the main cervical thyroid proves a unique challenge for resection. A trans-cervical approach is preferred but may be hazardous due to the possibility of ectopic thyroid tissue with alternate blood supply. Presentation of case: A 72 year old female who had a previous left hemithyroidectomy presents with a symptomatic central substernal thyroid mass. Following radiological work-up, the separate goitre was carefully removed via a trans-cervical approach and avoidance of sternotomy. She had a rapid recovery without complication. Discussion: The anatomy and embryology of substernal masses need to be carefully considered particularly if the mass is ectopic thyroid tissue. Careful pre-operative assessment may determine its nature and anatomical features. Intra-operative dissection requires consideration of blood supply and surrounding structures, but often may be and is best completed via a cervical approach to minimise morbidity. Review of the literature affirms the preference for a trans-cervical approach and offers criteria for successful resection via this method. Conclusion: Confirming the nature and anatomy of a separate substernal goitre enables successful removal of the mass via a trans-cervical approach with minimal morbidity.